MEDIASI KENYAMANAN BERWISATA PADA PENGARUH PENERAPAN PROGRAM CHSE TERHADAP KEPUASAN WISATAWAN - YADNYA, I WAYAN ADITYA NURSANA; GANDHIADI, G.K.; SARI, KARTIKA (E-Jurnal Matematika; Vol 12 No 1 (2023), 2023)
The COVID-19 had a major effect in Indonesia, specifically in the tourism sector. The government has made efforts to guarantee comfort during a pandemic by launching a CHSE certification program for tourism businesses. Our research aims to study the effect of implementing the CHSE program on tourist satisfaction at the Monkey Forest Ubud. The method used is partial least square structural equation modeling with three constructs namely tourist satisfaction, travel comfort and implementation of the CHSE. The implementation of the CHSE is structured by four constructs, namely the cleanliness, health, safety, and environmental sustainability constructs. The results obtained that the implementation of the CHSE program has a significant influence on tourist satisfaction through the convenience of visiting the DTW Monkey Forest Ubud with an indirect effect path coefficient is 0.345